THE IMPACT OF DIGITAL TRANSFORMATION ON STRATEGIC MANAGEMENT - Adrian George BOZINTAN; Emil Lucian CRIȘAN; Ory PINCO (Annals of the University of Oradea: Economic Science)
Currently, there are many discussions about the impact of digital transformation on company management, with success primarily reliant on firms’ ability to adapt to new market demands. Consequently, to maintain their positions or to evolve, companies across all industries need to regularly update their structures and ideals in line with digital transformation. Although the precise definition of digital transformation is still unclear, as evidenced by inconsistencies in the literature, it is already influencing management practices carried out by companies. The goal of this paper is to analyze the impact of digital transformation, with its highly dynamic characteristics, on strategic management. In this sense, we perform a literature review of the papers which describe how the two topics are related. We discover that strategic management has evolved in response to digital transformation as conventional managerial practices nowadays would no longer work at maximum efficiency. Strategic management has changed, adopting new features, most notably faster decision-making and less arduous tasks for top managers, allowing them to focus exclusively on performing tasks that match their specific competencies. These results are useful for both practitioners and researchers in performing their daily strategic management activities, and research efforts, respectively.